(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The importance of power density and converter efficiency is growing in the electric car industry. Losing weight is one way to lower the power consumption of an electric car. An efficient DC-DC bidirectional converter (12V to 48V) with a power density of 1.5 kW is demonstrated in this dissertation report. This converter made use of planar magnetics, a substrate with thermal conductivity, and cooling semiconductors with two sides. The design of the converter was a double interleaved boost based on an interphase transformer. To guarantee that power could flow in both directions, the circuit’s design included a full bridge. Magnetic cores, capacitors, heat sinks, and connections were all part of the semiconductor devices that were optimized for electrical, mechanical, and thermal aspects. The use of a thermal clad board allowed for the symmetry of the power circuit and the reduction of parasitic impedance. The efficiency of the dual interleaved boost converter was tested in both static and dynamic modes of operation. Theory and criteria were satisfied by all waveforms. Coil current sharing and strong coupling are features of the planar interphase transformer. Design predictions for temperature and power loss were met by a number of components. The efficiency of both the boost and buck modes was 94% under the rated condition. With and without heat sinks, the power densities were 1.8 kW/liter and 5.1 kW/liter, respectively. An example of how commercially available components can achieve high efficiency and power density is demonstrated by the proposed converter. This converter allows an electric vehicle to attach additional loads to its 12V battery. Aircraft and electric ships both use it for the same purpose.